A bibliometric analysis of coconut sap research - Awang, Anis Fadhlina Izyani; Sheikh Mohamed, Hassan Ibrahim; Mohamad Nor, Maryana; Saidan, Noor Hafizoh; Zainurin, Nurul Amira (Nutrition Society of Malaysia (NSM), 2023)
Introduction: Coconut sap is a sweet, fragrant liquid obtained from the inflorescence of coconut tree. In this study, a literature search was conducted using the Scopus database to study the trends of coconut sap research. Methods: Data extracted from the Scopus database were analysed and visualised using VOSviewer to determine top authors, papers, countries, collaborations, and research areas. A total of 76 publications up to year 2021 were identified and refined using keywords of “coconut sap”, “coconut sugar”, “coconut inflorescence”, “coconut inflorescence sap”, “coconut neera”, and “Cocos nucifera”. Results: Based on the analysis, research on coconut sap started in 1984, with a total of 53 authors, nine countries, and 12 sources that had published more than two documents. The analysis of countries and sources revealed that India and IOP Conference Series: Earth and Environmental Science (EES) were the most prolific country and sources, respectively. The most influential document was on the chemical compositions and bacteriology of coconut sap. The results also showed that research on coconut sap was in the field of food processing during the early years, followed by fermentation, agriculture, and bacteriology of coconut sap. Research on coconut sap’s bacteriology started in 1986 and became a major interest, especially among high impact journals. Conclusion: Overall, coconut sap is a potential target for the development of nutraceutical products, especially in the food and beverage industry.